(untitled) (Journal of Asian Geography, 2024)
The connection between people and the environment has been blamed for changes. Planning for sustainable development requires awareness of land use and land cover (LULC), its severity, causes, and implications. The purpose of this study was to generate maps that illustrate the land use and land cover within the Kwahu West Municipality and detect changes to identify and analyse overall patterns in LULC changes in the area. This research employed remote sensing techniques to assess land use and land cover alterations (LULC). This study used Landsat 7 Enhanced Thematic Mapper (ETM+) images from 2001, Landsat 8 Operational Land Imager (OLI) and Thermal Infrared Sensor (TIRS) images from 2015, and Landsat 8 Operational Land Imager (OLI) and Thermal Infrared Sensor (TIRS) images from 2023 to detect and quantify LULC changes that occurred over a 22-year study period. Arc GIS 10.8 and ERDAS Envision 13 were used to pre-process the data. According to the study, built-up land and bare land rose in their respective areas and years by 10.675 km2 (or 2%), 18.421 km2 (or 5%), and 29.096 km (or 7%), respectively, between 2001 and 2015 and 2015 and 2023. The overall change from 2001 to 2023 was correspondingly 29.096 km. The results depicted a drastic change in the study area's forest vegetation, which can be attributed to a sharp rise in population, urbanisation, and other infrastructure projects. These changes have been determined to cause biodiversity loss and water contamination. It is recommended that the Municipality's Lands Commission initiate a public education campaign about creating local planning schemes for lands, especially in undeveloped and underdeveloped areas.